Political Roasting as Social Criticism: Social Actor Strategies in Kiky Saputri’s Resolusi Indonesia - Syahputra, Alviego Fachrul; Yesicha, Chelsy (UIR Press, 2026)
Previous studies have examined political humor using Fairclough's critical discourse analysis or investigated social actor representation in news discourse through van Leeuwen's framework. However, little attention has been paid to how political roasting on mainstream television constructs social actor representation through the simultaneous use of inclusion and exclusion strategies. More importantly, existing studies rarely explain how these discursive strategies negotiate the tension between political criticism, media institutions, and symbolic power. This study addresses this gap by examining Kiky Saputri's political roasting in Resolusi Indonesia through Theo van Leeuwen's social actor representation framework.This study aims to analyze the social actor representation strategies in the political roasting delivered by Kiky Saputri in the ‘Resolusi Indonesia’ program at Metro Tv. The Focus is on the application of exclusion and inclusion strategies based on Theo van Leeuwen’s social representation theory. This research employed a qualitative method with critical discourse analysis approach, particularly the inclusion and exclusion strategies. Data were collected through documentation of the program’s recordings and analyzed to identify forms of representation and the meanings constructed. The findings show that Kiky Saputri tends to use inclusion strategies to highlight the involvement of the political elite, while employing exclusion strategies to obscure or reduce the legitimacy of that group. These results indicate that political roasting can serve as an effective medium for social criticism, though still bound by mainstream media discourse. This research contributes to political communication studies by offering new perspectives on comedy’s role in shaping public opinion.